Protocolo de intervención en conductas suicidas - Villacrés Vivanco, Cardari Michelle (My University, 2021)
Suicidal behavior is a set of ideas and actions directed by the subject himself that lead to death or a situation of mortal gravity. Around 800,000 people die annually from this phenomenon around the world; despite these alarming figures, there is no abundant and complete information on the role of the psychologist in this situation. In accordance with this panorama, being a matter of worldwide concern, the present investigative work aimed to describe the protocol of psychological intervention in suicidal behavior, which will serve as a guide for health professionals and people in academic training, the methodology responds to a descriptive bibliographic review of books and specialized articles. According to the research, it was possible to establish that in the intervention protocol in suicidal behavior the main strategies used by professionals come from the Cognitive Behavioral model, which consists of inquiring about thoughts, feelings and emotions, supportive social networks and empathy to understand the inner world of the subject; Likewise, from the results of the reviewed studies, the relevance of active contact between therapist and patient and multidisciplinary work between professionals with careers related to Mental Health is rescued, this to avoid repeat behaviors of this behavior. Finally, as a recommendation it is important to point out the preparation and training of the psychologist in social skills, establishments of empathy, control of emotions and containment strategies, because this modifies the responses of the treating individual.
La conducta suicida es un conjunto de ideas y acciones dirigidas por el propio sujeto que conducen a la muerte o a una situación de gravedad mortal. Alrededor de 800.000 personas mueren anualmente a causa de este fenómeno en todo el mundo; a pesar de estas cifras alarmantes no existe información abundante y completa sobre el rol del psicólogo frente a esta situación. De acuerdo con este panorama, siendo un tema de preocupación mundial, el presente trabajo investigativo tuvo como objetivo describir el protocolo de intervención psicológica en la conducta suicida, el que servirá de guía para los profesionales sanitarios y personas en formación académica, la metodología responde a una revisión bibliográfica de tipo descriptiva de libros y artículos especializados. De acuerdo con la investigación se pudo establecer que en el protocolo de intervención en la conducta suicida las principales estrategias que utilizan los profesionales provienen del modelo Cognitivo Conductual que consiste en indagar sobre pensamientos, sentimientos y emociones, redes sociales de apoyo y la empatía para comprender el mundo interior del sujeto; asimismo de los resultados de los estudios revisados se rescata la relevancia del contacto activo entre terapeuta y paciente y el trabajo multidisciplinario entre profesionales con carreras afines a la Salud Mental, esto para evitar comportamientos reincidentes de esta conducta. Finalmente, como recomendación es importante señalar la preparación y capacitación del psicólogo en habilidades sociales, establecimientos de empatía, control de emociones y estrategias de contención, en razón de que esto modifica las respuestas del individuo tratante.
Keywords: CONDUCTA SUICIDA; INTERVENCION; PSICOLOGICA; COGNITIVO CONDUCTUAL